Bibliometric Study of Waste Bank - Winarsih, Winarsih; Suyadi, Suyadi; Efani, Anthon; Yanuwiadi, Bagyo (Proceeding of International Joint Conference on UNESA, 2024)
Bibliometrics is a statistical analysis of books, journals, articles, or other publications. Bibliometric research aims to measure outcomes, institutions, and countries of origin of researchers and map the development of scientific disciplines in new fields of science and technology. This study aims to determine trends in waste bank article writing and mapping in searching for trends in international scientific publications using the Scopus database. The bibliometric analysis method in this study was carried out using the Publish or Perish software with the keywords Waste Bank, and the article results were then grouped based on the author's profile, published article data, and the journal chosen to publish the article; then, data analysis was carried out using the VOSviewer software. This research found that for ten years from 2013-2022, articles regarding waste banks that were successfully identified totaled 92 articles. The most published articles were in 2019, with 19 pieces. The journal that has issued the most reports on waste banks is the Journal IOP Conference Series: Earth and Environmental Science which contains 21 articles. The article entitled Community-based solid waste bank program for municipal solid waste management improvement in Indonesia: a case study of Padang City has the highest number of citations, namely 41. The results of the mapping analysis using the VOSViewer software have three themes, namely "waste management policy," "solution," and "circular economy," which are still rarely researched and are the latest themes in research.